Labor trafficking among migrant populations: a scoping review and qualitative interview study with stakeholders - Fernández-Sánchez, Higinio; James, Jessica; Zahoui, Ziad; Ging, Luke; Vásquez-Ventura, Ingrid; Stockton, Jennifer; Santa Maria, Diane (Frontiers in Human Dynamics, 2025)
IntroductionLabor trafficking is a widespread yet underreported form of exploitation that disproportionately affects migrant populations. Migrants often face coercion, deception, and abuse across various labor sectors, and these circumstances are often exacerbated by structural inequalities and legal protections. There is a pressing need to synthesize existing knowledge and integrate stakeholders’ perspectives to inform future prevention and policies.ObjectiveThis study examines the scope, nature, and thematic trends in the literature on labor trafficking among migrant populations and augments these findings with qualitative insights from stakeholders working directly with trafficked migrant populations.MethodsA scoping review was conducted following A scoping review was conducted according to the PRISMA guidelines. Nineteen peer-reviewed empirical studies published between 2014 and 2024 were analyzed across four databases. In parallel, 17 semi-structured interviews were conducted with service providers, researchers, and advocates experienced in labor trafficking. Structural violence theory guided the thematic analysis using Quirkos software.ResultsSeven major themes emerged: (1) informal recruitment networks, (2) hazardous and exploitative working conditions, (3) psychological and physical coercion, (4) economic and structural vulnerability, (5) gender-based vulnerabilities, (6) inadequate legal protections and enforcement gaps, and (7) mental health impacts. The qualitative data highlight the lived realities and systemic challenges trafficked migrants face and help validate and enrich the findings from the scoping review.ConclusionLabor trafficking among migrants is driven by economic, legal, and social vulnerabilities. Comprehensive, survivor-centered policies are urgently needed: reforms to recruitment practices, expanded mental health support, and stronger legal frameworks. The study findings call for cross-sectoral collaboration and the integration of migrant voices in program and policy design to combat trafficking for labor exploitation.